Profesionalisme Guru dalam Integrasi Teknologi: Pilar Penguatan Mutu Pendidikan dalam Sistem Manajemen Pendidikan Nasional: Penelitian - Hariyani Prasetyaningtyas; Rahmat Rizki Basuki; Siti Zulaikha; Muh. Takdir (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the forms of teacher professionalism in integrating information and communication technology (ICT) into teaching practices as a strategy to enhance the quality of national education. This research employs a qualitative descriptive approach through a literature review of relevant academic sources, particularly those discussing the Technological Pedagogical Content Knowledge (TPACK) framework. The findings reveal that teacher professionalism is reflected in various activities such as designing TPACK-based lessons, utilizing interactive digital media, participating in ICT training, developing digital teaching portfolios, and collaborating in digital design teams. ICT integration by teachers has a transformative effect on the learning process, enabling personalization, flexibility, and the promotion of students’ digital literacy and ethics. The study highlights TPACK as the foundational framework for building 21st-century teacher competencies that are adaptive to technological advancements. Therefore, sustainable strategies such as TPACK-based training, strengthening digital teacher communities of practice, equitable infrastructure, and providing incentives and certifications for digitally innovative teachers are recommended to reinforce ICT integration in the national education system.